2014
DOI: 10.1186/1687-6180-2014-58
|View full text |Cite
|
Sign up to set email alerts
|

Modeling individual HRTF tensor using high-order partial least squares

Abstract: A tensor is used to describe head-related transfer functions (HRTFs) depending on frequencies, sound directions, and anthropometric parameters. It keeps the multi-dimensional structure of measured HRTFs. To construct a multi-linear HRTF personalization model, an individual core tensor is extracted from the original HRTFs using high-order singular value decomposition (HOSVD). The individual core tensor in lower-dimensional space acts as the output of the multi-linear model. Some key anthropometric parameters as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Although our results are slightly better than [174], they are lower than [172], which is -according to our research-the smallest score reported among studies using MSD. Finally, in general, tensor-based approaches [176,175,177,178] perform better than PCA-based methods, reaching their best performance at 3.5 dB in the frequency band 50 Hz -8 kHz [178], which is comparable to our results in the frequency band 0.2 -8 kHz (2.9 dB, σ = 0.0735).…”
Section: Although the Relatively Highsupporting
confidence: 86%
See 2 more Smart Citations
“…Although our results are slightly better than [174], they are lower than [172], which is -according to our research-the smallest score reported among studies using MSD. Finally, in general, tensor-based approaches [176,175,177,178] perform better than PCA-based methods, reaching their best performance at 3.5 dB in the frequency band 50 Hz -8 kHz [178], which is comparable to our results in the frequency band 0.2 -8 kHz (2.9 dB, σ = 0.0735).…”
Section: Although the Relatively Highsupporting
confidence: 86%
“…A single linear regression model is used for mapping anthropometric features to a five-dimensional vector obtained by means of N-mode Singular Value Decomposition (N-mode SVD) and which represents the subject mode in the tensor. A similar tensor-based approach is used in [175] and [177], but to construct the regression model, they employed an ANN and high-order partial least squares, respectively.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Algazi et al [93] suggested using a number of one-dimensional anthropometric measurements for HRTF fitting through regression methods or other machine learning techniques. This approach was recently pursued in a number of studies [126][127][128][129] investigating the correspondence between anthropometric parameters and HRTF shape. When suitable processing is performed on HRTFs, clear relations with anthropometry emerge.…”
Section: Wireless Communications and Mobile Computingmentioning
confidence: 99%
“…In fact, most of the experimental data describe the relations between multi-way input and multi-way output which are deemed as tensors. In order to adjust this kind of data, a new prediction model, higher order partial least squares (HOPLS), was proposed [7,8]. HOPLS is highly suitable for building a prediction model which has tensor-input and tensor-output.…”
Section: Introductionmentioning
confidence: 99%